Coefficient Estimates for a Subclass of Bi-Univalent Strongly Quasi-Starlike Functions (Communications in Mathematical Research, 2019)
The aim of this paper is to establish the Fekete-Szegö inequality for asubclass of bi-univalent strongly quasi-starlike functions which is defined in the openunit disk. Furthermore, the coefficients $a_2$ and $a_3$ for functions in this new subclassare estimated.